How to deal with covert child labour, and give children an effective education, in a poor developing country: An optimal taxation problem with moral hazard - Alessandro Cigno (Center for Economic Studies and ifo Institute (CESifo), 2010)
Given that credit and insurance markets are imperfect, and given also that intra-household transfers, and much of the work a child does, are private information, the second-best policy uses a combination of need and merit based education awards, together with a mix of taxes on parental income, and on the return to educational investment. It also makes school enrollment compulsory and, if the child wage rate is sufficiently high, sets a ceiling, decreasing in parental income, on overt child labour.
Keywords: D82; H21; H31; I28; J24; 330; child labour; education; uncertainty; moral hazard; Kinderarbeit; Haushaltsökonomik; Optimale Besteuerung; Bildungsverhalten; Moral Hazard; Schulfinanzierung; Subvention; Second Best; Theorie